Pedagogy of peers: Cultivating writing retreats as communities of academic writing practice - Benvenuti, S. (South African Journal of Higher Education, 2017)
Pressure related to research publication output continues, heightened by growing numbers of early career academics. Writing retreats, designed around the pedagogy of community of practice, have potential to initiate early career academics into core academic practices including peer review, and draw them into the community of ‘academics as writers’. However, a series of four semi-structured writing retreats based on this pedagogy revealed that supporting novice writers’ trajectory of progress from peripheral through to expert participation is challenging. Careful attention must be paid to balancing the design of the retreat, the ‘construction’ of the retreat community of practice and the engagement of participants on retreat. Skilfully managed, these writing retreats can support academic writing development, and deliver benefits to academics, from novice to established, that include enhanced research publication output, strengthened academic identity as writers and a motivated community of practice extending beyond the writing retreats.